University Social Responsibility at the Faculty of Agricultural Sciences: The internal stakeholders (Revista Electrónica Calidad en la Educación Superior, 2020)
The objective of the research was to evaluate the level of university social responsibility and the perception of its stakeholders, interns of the Universidad Nacional Jorge Basadre Grohmann in Tacna. Two instruments were designed to analyze university social responsibility management and the level of perception of internal stakeholders. Through a representative sample of 26 internal stakeholders. The results indicated that 58% mentioned that the resources allocated to the university are well used, 63% valued the possibility of developing skills as researchers during their training, 50% of the students participated in activities organized by the university. In the checklist, an average score of 72.18, 70.00 and 58.2 was obtained for students, teachers and administrators.
Keywords: University Social Responsibility; internal actors; internal stakeholders; perception